The Hotel Avocado / Bob Mortimer. - Mortimer, Bob, 1959- (Gallery Books UK, 2025)
Gary Thorn is struggling with a big decision. Should he stay in London, wallowing in the safety of his legal job in Peckham and eating pies with his next door neighbour, Grace and her dog Lassoo, or should he move to Brighton, where his girlfriend Emily is about to open The Hotel Avocado? Either way, he'd be letting someone down. But sinister forces are gathering in a cloud of launderette scented-vape smoke, and the arrival of the mysterious Mr Sequence puts Gary in an even worse predicament: soon he might be dead. All Gary wants is a happy life. But he also wants to be alive to enjoy it.